Tumor phantom model for MRI-guided focused ultrasound ablation studies - Antoniou, Anastasia; Evripidou, Nikolas; Georgiou, Leonidas; Chrysanthou, Antreas; Ioannides, Cleanthis; Damianou, Christakis A. (My University, 2023)
Background:The persistent development of focused ultrasound (FUS) thermaltherapy in the context of oncology creates the need for tissue-mimicking tumorphantom models for early-stage experimentation and evaluation of relevantsystems and protocols.Purpose:This study presents the development and evaluation of a tumor-bearing tissue phantom model for testing magnetic resonance imaging(MRI)-guided FUS (MRgFUS) ablation protocols and equipment based on MRthermometry.Methods:Normal tissue was mimicked by a pure agar gel, while the tumorsimulator was differentiated from the surrounding material by including sili-con dioxide. The phantom was characterized in terms of acoustic, thermal, andMRI properties. US, MRI, and computed tomography (CT) images of the phan-tom were acquired to assess the contrast between the two compartments. Thephantom’s response to thermal heating was investigated by performing highpower sonications with a 2.4 MHz single element spherically focused ultrasonictransducer in a 3T MRI scanner.Results:The estimated phantom properties fall within the range of literature-reported values of soft tissues. The inclusion of silicon dioxide in the tumormaterial offered excellent tumor visualization in US,MRI,and CT.MR thermom-etry revealed temperature elevations in the phantom to ablation levels and clearevidence of larger heat accumulation within the tumor owing to the inclusion ofsilicon dioxide.Conclusion:Overall, the study findings suggest that the proposed tumorphantom model constitutes a simple and inexpensive tool for preclinical MRg-FUS ablation studies, and potentially other image-guided thermal ablationapplications upon minimal modifications.
Keywords: MRI; Ablation; Focused ultrasound; Phantom; Thermometry; Tumor